Statistical variations in predicted martensite variant volume fractions in superelastically deformed NiTi modeled using habit plane variants versus correspondence variants. (15th June 2021) - Sridhar, Shivram Kashyap; Stebner, Aaron P.; Rollett, Anthony D.
Abstract: Habit plane variants (HPVs) are traditionally used as the fundamental microstructure unit in micromechanical models of shape memory alloys. Recently, an approach using Correspondence Variants (CVs) has emerged. Previous research has shown that HPVs cannot completely explain superelastic deformation of Nitinol, especially beyond initiation of the martensitic phase transformation that gives rise to superelasticity. In this work, a statistical comparison of both modeling approaches is presented for the case of superelastic Nitinol subjected to uniaxial tension and uniaxial compression. Specifically, volume fractions of variants that contribute to deformation were calculated using the two models and then compared. The relative differences were found to be about 30% in tension and 10% in compression at high strains. Allowing detwinning to occur in the HPV model reduced the relative differences in CV volume fractions to about 20% in tension.